(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Mathematics is an essential part of the number of subjects taught formerly from early childhood education to secondary level. Use of proper teaching learning materials is essential in the transaction of the mathematical concepts. Textbooks are largely the main resources in teaching–learning processes in many situations and especially in the remote parts of the country. In mathematical teaching Piagetian constructivism of knowledge focuses on activities of interest while Vygotsky stresses on social construction of knowledge. Hence the TLM-Textbooks should be sensitive to the diverse context from which the learners come and in which they learn. In this article the an attempt to develop a framework for analysis of mathematics–grade -3 textbook-Ganit ka Jadoo, from pedagogical and socio-cultural perspectives. Parameters for analyzing the content presented in the textbook were identified from insights provided by Shulman in his presentation of Pedagogical Content knowledge, where he emphasized on combining content of the subject and the pedagogy involved to present the content to be analyzed from pedagogical perspective. Similarly inputs about socio-cultural perspective by Vygotsky aided in develop an understanding how individuals attain their knowledge from community. In this study an attempt is also made to refer to the learning outcome presented by NCERT and to analyze presentation of the concepts with reference to the parameters and to locate the representation of socio cultural perspective in the text.